How do children with Tourette’s syndrome and their caregivers live with the disorder? A systematic review of qualitative evidence - Suh, Hyo-Weon; Yoon, Seok-In; Hong, Sunggyu; Lee, Hyun Woo; Lee, Misun; Kim, Jong Woo; Chung, Sun-Yong (Frontiers in Psychiatry, 2022)
Background Tourette’s syndrome (TS) is a childhood neurodevelopmental disorder characterized by sudden, repetitive, involuntary, and irregular muscle movement and vocalization. Recently, non-pharmaceutical methods, such as behavioral therapy, psychotherapy, and deep brain stimulation, have been introduced as alternatives to pharmacological treatment for TS. This study aimed to systematically review and synthesize qualitative evidence on the experiences of children with TS and their caregivers. A meta-synthesis of qualitative evidence could help provide a comprehensive understanding of the challenges experienced by children with TS and their caregivers with the aim of providing more effective treatment and services for them. Materials and methods A systematic search was conducted using MEDLINE/PubMed, EMBASE, Cumulative Index to Nursing and Allied Health Literature, PsycARTICLES, and three Korean databases (Korean Medical Database, Research Information Sharing Service, and ScienceON) in July 2021. Studies were included if they collected and analyzed qualitative data from children with tic disorder or TS, or their caregivers. Qualitative research findings on the experiences and perspectives of children with TS and their caregivers were critically appraised and synthesized using the Joanna Briggs Institute methodology. Results Eight eligible studies were included. The findings from these studies (i.e., themes or subthemes of qualitative research) were aggregated into categories (a group of similar findings) and synthesized findings (a group of categorized findings). Ultimately, the 60 findings were aggregated into 15 categories. Finally, four synthesized findings were derived from the 15 categories: (i) continuation of challenging daily life, (ii) denying that TS causes emotional distress, (iii) accepting and understanding TS as part of oneself, and (iv) looking to the future. Conclusion Children with TS and their caregivers experience physical and psychological distress and social deprivation. Avoiding and suppressing TS causes secondary distress such as guilt. However, seeking social support and accepting the disorder reduce the distress caused by symptoms and lays the foundation for later growth. Even in the face of adversity, children with TS and their caregivers find personal value and acquire a more open and optimistic attitude toward life. This review shows that acceptance-based therapy and social support should be provided for the treatment and management of TS.